Mini avaliação nutricional (MAN) e índice de massa corporal (IMC) em idosas de uma unidade municipal de saúde - MOURA, Luana Helena Nogueira (2023)
Aging is a natural and individual process, which causes a series of physiological, metabolic, anatomical, social and psychological changes, which manifest themselves in structural and functional changes. The aim of this study was to assess the nutritional status, through the Mini Nutritional Assessment (MNA) and the Body Mass Index (BMI), in a group of elderly women who attended at the Municipal Health Unit (UMS) in Guamá in Belém, Pará. This is a descriptive, cross-sectional study and the research was conducted in August 2019 after being approved by the Research Ethics Committee of the Federal University of Pará (UFPA). Data collection was performed with 16 elderly women with a mean age of 72.18土8.47 years; the results found in the MNA were 56.25% (n=9) of the elderly were in normal nutritional status, 37.5% (n=6) were at risk of malnutrition and 6.25% (n=1) were malnourished. The results of the BMI were 37.5% (n=6) were underweight, 31.25% (n=5) eutrophic and 31.25% (n=5) overweight. As conclusion, there is an importance of studies in this area, because the role of nutrition in this stage of life is to maintain the proper functioning of the body, maintenance of health and nutritional needs, and better quality of life.